Essays in development economics: the role of property rights on labour supply and land markets - AYALA-CANTU, LUCIANO (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2020)
The process of economic development requires that an economy moves from an agriculture-intensive setting to a more industrialized situation. It is then essential that agricultural productivity increases and shifts to a more capital-intensive production system, hence allowing labour to be transferred from agriculture to other sectors of the economy (Gollin et al, 2002). Property rights are a key part of this process for several reasons. First, tenure security enhances incentives for investment and therefore increases agricultural productivity. Second, households with financial constraints are able to use their assets as collaterals, increasing their credit access to undertake entrepreneurial activities. Third, property rights enable the functioning of land markets without significant transaction costs. This allows for land to be transfer to the best-suited candidates, improving overall efficiency. Also, land markets allow households with a comparative advantage in the non-farm economy to gradually move out of agriculture. This thesis provides empirical evidence on the role of land institutions on household labour supply, land rental markets, gender equality and agricultural production. In the second chapter, we explore the effects of land certificates in women's participation in rental markets in Vietnam. Our results suggest women are less likely to receive any type of compensation (monetary or in-kind) when renting land out to their relatives. The third chapter analyses the impact of the Vietnamese Land Law of 2013, which increased the duration of usage rights for annual land from 20 to 50 years, in household labour supply and agricultural production. The policy change led to a reduction in own-farm labour supply, and an increase in the capital usage. The fourth chapter explores the effect of nation-wide land certification program in Mexico. The results suggest that households participating in the program reduced their hours of wage employment and increase their cultivated land. Although we did not find evidence of an increase in own-farm labour, the evidence suggests that households in the certification program reduce the number of children working in their farms.
APPROVED
Keywords: economic development; property rights; land markets; labour markets; gender; tenure security; Mexico; Vietnam; land titles